KETERAMPILAN MAHASISWA DALAM MENGIKUTI PERKULIAHAN (Studi pada Program Studi Bimbingan dan Konseling Angkatan 2012) - Alfiani, Rina; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
Â This problems based on phenomena that researcher found in the field. Some of college students have difficulty on following study in the class. So, researcher interests to raise the problems about college studentâs aptitude on following study in the class (study at college studentâs 2012 guidance and counseling program). Purpose of this research try to describe: (1) studentâs ability in reading book. (2) Studentâs ability in noticing material. (3) Studentâs ability in study at the class. (4)studentâs ability in following examination. This research was descriptive research that try to describe the way thing are. The population on this research was all 2012 college students of guidance and counseling STKIP PGRI West Sumatra. The total of population was 279 students. To take the sample researcher use proportional random sampling. So, the sample of this research to be 74 students. Instrument that used was questionnaire meanwhile for data analysis used percentage technique. The result of this research describe that: (1) studentâs ability in reading book based on planning and strategy was less capability categorized. (2) Studentâs noticing the material also less capability categorize. (3) Studentâs attending the study at the class based on positive attitude less capability,(4) studentâs ability in noticing material from enough sleep and rest also showed that less capability.